Reliability and Relationship Between 2 Measurements of Transversus Abdominis Dimension Taken During an Abdominal Drawing-in Maneuver Using a Novel Approach of Ultrasound Imaging - Jhu, Jhong-Lin; Chai, Huei-Ming; Jan, Mei-Hwa; Wang, Chung-Li; Shau, Yio-Wha; Wang, Shwu-Fen (The journal of orthopaedic and sports physical therapy, 2010)
Reliability study of clinical measurement. The primary purpose was to develop a reliable method for measuring muscle length changes of the transversus abdominis (TrA) during contraction. The secondary purpose was to investigate the relationship between changes in thickness and length (as indicated by the lateral sliding of the anterior muscle-fascia junction) of the TrA muscle during an abdominal drawing-in maneuver. We also provide data on between-day reliability of change in thickness (ΔT) of the TrA. Ultrasound imaging measurements of TrA thickness at rest (Thr) and during maximal contraction (Thm) have been shown to be reliable. However, limited data exist on quantifying changes in TrA length (as indicated by the lateral sliding of the muscle-fascia junction [Δx]) and ΔT during contraction. Eighteen healthy adults (mean ± SD age, 22.6 ± 2.5 years) participated in this study. Brightness mode ultrasound images of the TrA were collected at rest and during an abdominal drawing-in maneuver. Subjects were examined by the same examiner twice within a 48-hour period. ΔT, ΔT/Thr, Thr, Thm, and Δx of the TrA were calculated. Medial-lateral movement of the transducer during measurement was corrected through a custom-written program that used an internal marker created by an echo-absorptive thread attached to the skin. Intraclass correlation coefficients (ICC3,1), within-subject coefficient of variance, and standard error of measurement were calculated. The relationship between ΔT and adjusted Δx of the TrA muscle was investigated. The ICC values for Thr, Thm, and ΔT of the TrA muscle were greater than 0.75, with the exception of the left ΔT (0.62) and left ΔT/Thr (0.49). After adjusting for medial-lateral motion of the transducer, the ICC values of adjusted Δx were above 0.75, and the within-subject coefficient of variance was below 10%. There was no significant correlation between ΔT and adjusted Δx of the TrA. Ultrasound imaging measurements of TrA thickness and length change were shown to be reliable using a novel method to control for medial-lateral transducer motion. Measuring different but unrelated dimensional changes in the TrA might provide further insight as to the function of the TrA.